Effect of Fractions of Barleria Buxifolia and their Biological Activity Against Economically Important Lepidopteron Pests - Jeyasankar, A; Chinnamani, T (International Journal of Natural Sciences Research, 2017)
Antifeedant, larvicidal and ovicidal activities of fractions isolated from ethyl acetate crude extracts of Barleriabuxifolia leaves were tested against fourth instar larvae of Spodopteralitura and Helicoverpaarmigera. The maximum antifeedant, ovicidal and larvicidal activity was recorded in fraction III of B. buxifolia against S. litura and H. armigera. Whereas significant larval mortality was observed in fraction III of B. buxifoliaon S. litura (78.66%) and H. armigera(73.76%) at the same concentration. These results indicate that B. buxifolia has the potential to serve as an alternate botanical pesticide in the management of Spodopteralitura and Helicoverpaarmigera.